Correlation of Patient-Reported Outcomes After Periacetabular Osteotomy With Femoral Head Coverage and Acetabular Orientation: A Single-Center Cohort Study. Issue 5 (April 2021) - Ibrahim, Mazen M.; Smit, Kevin; Poitras, Stéphane; Grammatopoulos, George; Beaulé, Paul E.
Background: Gaining a better understanding of the underlying pattern of acetabular dysplasia 3-dimensionally can help better guide treatment and optimize clinical outcomes after periacetabular osteotomy (PAO). Purpose: (1) To examine the relationship between femoral head coverage before and after PAO for dysplasia and patient-reported outcome measure (PROM) scores and (2) to assess if the direction/orientation of correction of the acetabulum can be predicted based on the Ottawa classification. Study Design: Cohort study; Level of evidence, 3. Methods: A retrospective analysis of a prospectively collected database from a single-center institutional registry of PAO was conducted, and PROM scores at a minimum of 2 years were analyzed. A total of 79 hips (67 patients [56 female]; mean age at surgery, 27.5 years [range, 15.8-53.7 years]) were available for inclusion. According to the Ottawa classification, 54 hips (68.4%) had global deficiency, 15 hips (18.9%) had posterior deficiency, and 10 hips (12.7%) had anterior deficiency. Hip2Norm software was used to analyze the 3-dimensional coverage of the femoral head. Statistical analysis was conducted to look at significant predictors of improvements in PROMs using the minimal clinically important difference (MCID) for the Hip disability and Osteoarthritis Outcome Score (HOOS) Activities of Daily Living subscale. Results: At a mean follow-up of 3.1 years (range, 2.0-7.4 years), all functional outcome scores improved significantly. A postoperative total femoral coverage <75.7%, posterior coverage (PC) <45.2%, and femoral head extrusion index >15.5% were all associated with not reaching the MCID for the HOOS Activities of Daily Living subscale. Multivariate analysis showed that PC was the single most important significant modifier influencing functional outcomes after PAO for the treatment of acetabular dysplasia, with an odds ratio of 6.0 (95% CI, 1.8-20.4; P = .004). One-way analysis of variance showed a significant difference comparing the mean change in radiographic measurements, that is, anterior coverage, PC, and total femoral coverage, per the Ottawa classification ( P < .001). Conclusion: Our study demonstrated that postoperative femoral head coverage and acetabular orientation were significant predictors of PROM scores. Classifying acetabular dysplasia into 3 groups based on the plane of instability could optimize the planning of PAO by giving a better understanding of the 3-dimensional deformity.